Aplikasi Sistem Informasi Geografis Kunjungan Wisatawan di Bali - I Gde Arya Aristha; I Nyoman Piarsa; Ni Kadek Ayu Wirdiani (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2017)
Increasing tourist arrivals in Bali should be followed by the preparation of the supporting factors of tourism. One of taurism support in Bali is spreading out tourist attraction in all Bali’s regency.Wide diployment and many tourist attraction cause less equalization on maintenance and promotion. The idea of Geographic Information System Applications Tourist Visits obtained byless inequality in the development of tourism in Bali. Application design utilize Google Maps asmaps provider. In this application is also equipped with features forecasting tourist visits.Forecasting is done by using least square method by processing number of tourist visitshistory. Result of application design is a application which can give information in text andimage of tourist attraction in entire Bali’s regency shown by infoWindow in each marker on map.Forecasting feature in geographical mapping application tourist visit be used for forecast number of visits coming.